The retirement project of George Stuart Atkins: development radio in the time of cybernetics. Issue 8 (17th November 2017) - Smillie, Ian
ABSTRACT: For years after its start-up in 1979, Farm Radio International (FRI) sent radio scripts and other material to broadcasters in more than 100 developing countries, believing it reached as many as 100 million people. By 2000, however, its unidirectional scattershot approach was being questioned by both communication specialists and its principal donor. Following a four-year struggle to reorganise its mission, programmes, and funding, FRI found new purpose, a new donor, and solid evidence of impact. The viewpoint offers lessons in management, communications for development, donor infatuation with "The Next Big Thing", the difference between information and knowledge, and how people learn.